Knowledge on Malaria and Health Seeking Behavior among the People of Belauri Municipality of Nepal: A Cross-sectional Study - Paudel, Ashok Kumar; Chhetri, Muni Raj; Panta, Prem Prasad; Luintel, Rashmi; BC, Sandhya (Journal of Karnali Academy of Health Sciences, 2023)
Background: Malaria infection is transmitted to humans through the bite of infected female Anopheles mosquitoes and 247 million cases of malaria in 2021, an increase from 245 million cases in 2020. The objective of the study was to assess the level of knowledge and health seeking behavior on malaria among the people of Belauri Municipality of Nepal. Method: A Cross-sectional descriptive study was done among randomly selected 387 households. Head of the households were the respondents for face to face interview. Pretested and validated tool was used for data collection. Statistical Package for Social Sciences version 20 used for data analysis. Percentages, frequency, bivariate and multivariate analysis has been to measure the distribution and level of association. Results: Overall knowledge about symptoms of malaria was good among 57.9% and who possessed a good understanding of malaria symptoms tended to seek treatment from modern health facilities during a malaria fever. Of these individuals, 43.8% sought treatment from public health facilities, while 32.7% sought treatment from private health facilities, resulting in a total of 76.5% seeking treatment from modern health facilities. However, the analysis found that the level of knowledge regarding malaria symptoms was not statistically significant (p=0.13) in relation to health-seeking behavior. Conclusions: For success of malaria prevention, programs should be designed to increase level of knowledge and also the translation of knowledge domain into appropriate health care seeking behavior in malaria fever.